Compact Optical Clock with 5×10−13 Instability at 1 s. Issue 1 (6th March 2018) - Phelps, Gretchen; Lemke, Nathan; Erickson, Christopher; Burke, John; Martin, Kyle
Abstract: We present a compact optical atomic clock design based on a two‐photon transition at 778 nm in rubidium that is capable of a frequency instability of 5×10 −13 at 1 s. The simple architecture occupies less than 30 L volume and currently uses commercial off‐the‐shelf components making this system an attractive, appealing, and competitive candidate to meet GPS‐III spacecraft frequency stability requirements. Copyright © 2018 Institute of Navigation.